Solid Substrate Fermentation of Cassava Peel for Poultry Feed Ingredient - ., Stephanie; T, Purwadaria (Indonesian Animal Sciences Society, 2013)
Cassava peel which is not used during cassava starch extraction is one of potential resources for animal feed. However, cassava peel has low level protein content, high level crude fiber, and high level of toxic cyanogenic compound. These problems limit the utilization of cassava peel as feed. Solid substrate fermentation using mold may be a solution process to increase its nutritional value and decrease toxic level of cassava peel. In this paper, matters that related with cassava peel fermentation process are subsequently described, namely: (i) problems of cassava peel; (ii) biodegradation and detoxification process; (iii) solid state fermentation methods on cassava peel; (iv) nutritional quality of fermented cassava peel; and (v) application of fermented cassava peel in poultry feed. The fermented cassava peel application is compared with those of cassava root and waste (onggok). Addition of nitrogen inorganic in the fermentation process increases the mold growth and protein content of the product, while fiber and cyanogenic contents are decreased due to mold degradation activity. The fermentation process may be carried out using only the cassava peel as the substrate or mixed with wheat flour, using indigenous microbes, Aspergillus niger or a white rot fungus, Panus tigrinus as inoculum. As well as fermented cassava root and waste, fermented cassava peel can be used to substitute maize as poultry feed, although it is reported that the optimum substitution in broiler ration is only 10%. Key words: Cassava peel, fermentation, nutritional value, poultry